PENGARUH PENYULUHAN GIZI SEIMBANG DENGAN MEDIA SOSIAL INSTAGRAM TERHADAP PENGETAHUAN, ASUPAN ENERGI DAN PROTEIN PADA REMAJA PUTRI SEKOLAH MENENGAH ATAS - Dwi Suryana, Ira; Mahmudah, Umi; Pusparini, Pusparini; Agung Suprihartono, Fred (Jurnal Gizi dan Dietetik, 2023)
Adolescent girls are at high risk of experiencing nutritional problems, one of which is chronic energy deficiency (CED). Inadequate nutrient intake during adolescence will have an impact on health in subsequent life stages, namely adulthood (pregnant mothers) and old age. One of the efforts that can be done to address nutritional problems in adolescent girls is to change their behaviors by enhancing their knowledge through nutrition education. One of the nutritional education media used for targeting adolescent girls is the social media platform Instagram. The aim of this research was to determine the effect of balanced nutrition counseling using the social media platform Instagram on knowledge, energy intake, and protein intake among high school adolescent girls. The intervention was conducted for a total of 9 days over a period of 18 days. This study is a quasi-experiment with a two-group pre-test and post-test design. The treatment group was provided with the social media platform Instagram, while the control group was provided with PowerPoint media. The sample size consisted of 64 participants divided into two groups: the treatment group and the control group, using purposive sampling method. The data were analyzed using the Wilcoxon test, Dependent t-test, Independent t-test, and Mann-Whitney test. The research findings revealed that there was an influence of nutrition counseling on knowledge, energy intake, and protein intake in the treatment group. Similarly, there was an influence of nutrition counseling on knowledge, energy intake, and protein intake in the control group. There was a difference in knowledge between the treatment group and the control group among adolescent girls. However, there was no difference in energy intake and protein intake between the treatment group and the control group among adolescent girls. Periodic and continuous nutrition counseling is necessary to observe significant changes in energy intake and protein intake.